2015
DOI: 10.1186/s12913-015-0935-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated clinical and quality improvement coaching in Son La Province, Vietnam: a model of building public sector capacity for sustainable HIV care delivery

Abstract: BackgroundThe global scale-up of antiretroviral therapy included extensive training and onsite support to build the capacity of HIV health care workers. However, traditional efforts aimed at strengthening knowledge and skills often are not successful at improving gaps in the key health systems required for sustaining high quality care.MethodsWe trained and mentored existing staff of the Son La provincial health department and provincial HIV clinic to work as a provincial coaching team (PCT) to provide integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In this study, documentation improved from 83% to 99% at the provincial level and from 54% to 97% at the district level. 16 In terms of ART retention, the 1 reporting study found no impact associated with the intervention, with no statistically significant difference in retention of postpartum women after 6 months in the intervention and control arms. 18…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…In this study, documentation improved from 83% to 99% at the provincial level and from 54% to 97% at the district level. 16 In terms of ART retention, the 1 reporting study found no impact associated with the intervention, with no statistically significant difference in retention of postpartum women after 6 months in the intervention and control arms. 18…”
Section: Resultsmentioning
confidence: 88%
“…One study reported a district level increased uptake of 62%–91% over 30 days. 16 In another setting, monthly ART initiation rose 185.5% after initiation of the intervention, from 179 initiations per month to 511. 19 ART adherence and retention were only reported in 1 study each.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…While the specific content and length of these trainings vary by country, they are all embedded into ongoing HIV quality programming activities and, wherever possible, make use of existing funding streams and QI and S&D-reduction curricula. On-site coaching and mentoring, a well-documented enabler of QI implementation,27 28 is provided by Ministries of Health and implementing partners (Cambodia, Vietnam) to guide sites in the analysis of data from HCWs and PLWH, and the development and testing of S&D-reduction interventions to address identified areas for improvement.…”
Section: Approachmentioning
confidence: 99%
“…3 As in other settings, training and on-site mentoring of clinic health workers has been a critical factor in the success of ART scale-up efforts. [4][5][6][7][8] This support has largely been delivered through collaborations between international organisations and national training institutions. However, the HIV response in Vietnam, as in many countries, is in a period of transition from a donor-supported programme to one supported and financed by national institutions.…”
Section: Introductionmentioning
confidence: 99%